2019
DOI: 10.1061/(asce)gt.1943-5606.0002147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic Temperature Variations on Thermal Response of an Energy Pile under a Residential Building

Abstract: The effects of daily cyclic temperature variations on the thermal response of an energy pile built under a six-level residential building are examined. The axial and radial thermal strains along the length of the pile followed stable, linear reversible paths during daily active heating and cooling cycles corresponding to a pile temperature range of 10 to 23°C (∆T of-8°C to 5°C) around a baseline temperature of 18°C. The stable responses of the thermal strains indicate that plastic deformations did not occur in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Previous experimental and analytical studies on the thermo-active pile foundation have shown that the temperature changes and thermal-induced stresses in the soil are not critical under the operating conditions of typical applications [8][9][10][11][12][13][14][15][16][17][18][19]. However, the temperature changes in the soil may become significant under extreme thermal loading conditions (up to 30 • C) due to intensive uses of the energy piles [12,14,15,18].…”
Section: Performacne Of Thermal-active Energy Pilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental and analytical studies on the thermo-active pile foundation have shown that the temperature changes and thermal-induced stresses in the soil are not critical under the operating conditions of typical applications [8][9][10][11][12][13][14][15][16][17][18][19]. However, the temperature changes in the soil may become significant under extreme thermal loading conditions (up to 30 • C) due to intensive uses of the energy piles [12,14,15,18].…”
Section: Performacne Of Thermal-active Energy Pilesmentioning
confidence: 99%
“…Similar thermal transfer analyses and temperature distribution studies were conducted extensively for thermo-active pile foundations [8][9][10][11][12][13][14][15][16][17][18][19]. In these studies, the pile was treated as a heat absorber for heat exchange between the ground surface and underground regions since the temperature at the ground surface fluctuates seasonally while the underground temperate remains constant.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies only focused on underground thermal energy utilization and heat transferring efficiency of the heat pump system, but studying the mechanical performance of the energy pile under the impact of varying temperatures is limited. Some investigations of the field energy pile have been conducted while subjecting it to monotonic heating or cooling [5][6][7][8][9][10][11][12][13][14][15][16][17]. Laloui et al [5] Sustainability 2021, 13, 7411 2 of 12 conducted a field test on a cast-in-place energy pile located in the Lausanne Institute of Technology; it was found that its average temperature was raised by 1 • C, generating an additional axial force of 100 kN.…”
Section: Introductionmentioning
confidence: 99%
“…Murphy and McCartney [10] have numerically investigated seasonal temperature variation, and it was observed that the mobilized side shear stresses nonlinearly change with the depth; the magnitudes of thermomechanical axial stresses were observed to increase most greatly near the toe of both foundations while being heated. Fewer field-scale evaluations on radial thermal reactions of energy pile were conducted [11,14,15]. It is found that the axial strain of the pile is smaller than the radial strain when the pile body expands or contracts.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research work, including experiments and numerical analyses, have been conducted on the temperature distribution and thermal mechanical behavior for thermo-active pile foundations [13][14][15][16][17][18][19]. However, the thermo-active pile foundation, which uses the pile as a heat absorber, is different from the proposed energy storage pile foundation system, where the pile is used as an energy storage medium through compressed air.…”
Section: Introductionmentioning
confidence: 99%